The Genexpress Index: a resource for gene discovery and the genic map of the human genome. - Houlgatte, R; Mariage-Samson, R; Duprat, S; Tessier, A; Bentolila, S; Lamy, B; Auffray, C (Genome Research, 1995)
Detailed analysis of a set of 18,698 sequences derived from both ends of 10,979 human skeletal muscle and brain cDNA clones defined 6676 functional families, characterized by their sequence signatures over 5750 distinct human gene transcripts. About half of these genes have been assigned to specific chromosomes utilizing 2733 eSTS markers, the polymerase chain reaction, and DNA from human-rodent somatic cell hybrids. Sequence and clone clustering and a functional classification together with comprehensive data base searches and annotations made it possible to develop extensive sequence and map cross-indexes, define electronic expression profiles, identify a new set of overlapping genes, and provide numerous new candidate genes for human pathologies.